THE INFLUENCE OF PARENTING PRACTICES AND CHARACTERS TOWARD SUBJECTIVE WELL-BEING IN ADOLESCENTS - Rahmi Yawmil Fauzi; Alfiasari; Yulina Eva Riany (Journal of Child, Family, and Consumer Studies, 2022)
Subjective well-being is considered one of the scientific measures to represent one's happiness and quality of life. This research aims to analyze the influences of parenting practices and characters toward subjective well-being in adolescents. This research used the explanatory method and was conducted in Bekasi, which was chosen based on a purposive approach. The respondents were 213 adolescents in the 11th grade of senior/vocational high school. The primary data was self-administered and collected through questionnaires. The collected data included adolescent characteristics (age and gender), family characteristics (parents' age, education, work status, and family size), parenting practices, characters, and subjective well-being. The data obtained were then processed and analyzed descriptively and inferentially using Microsoft Excel and SPSS 26. The results show that the parenting practices index and subjective well-being index were in a low category, while the character index was in the moderate category. The correlation test found that female adolescents tend to receive better parenting practices. Furthermore, significant correlations were also found among parenting practices, characters, and subjective well-being. This regression test found that parenting practices from the parents and adolescents’ characters significantly influence subjective well-being in adolescents.